Rare metal-ion metathesis of a tetrahedral Zn(ii) core of a noncentrosymmetric (3, 4)-connected 3D MOF. Issue 6 (15th January 2019) - Lee, Li-Wei; Kao, Ya-Chuan; Chung, Mei-Ying; Chang, Bor-Chen; Lee, Gene-Hsiang; Peng, Shie-Ming; Wang, Chih-Min; Liu, Yen-Hsiang; Lee, Sheng-Long; Lu, Kuang-Lieh
Abstract : An SHG-active framework of1-Zn can undergo metal metathesis, in which the tetrahedrally coordinated Zn(ii ) ions are completely exchanged with Cu(ii ) ions while retaining the integrity of the network. Abstract : An SHG-active noncentrosymmetric (3, 4)-connected Zn(ii )–organic framework, {[Zn2 (4-abpt)(3, 4-pydc)2 ]·2DMAc·3MeOH·H2 O} n (1-Zn ), was synthesized using a mixed-ligand system. The1-Zn framework undergoes metal metathesis, with the complete exchange of the tetrahedrally coordinated Zn II ions with Cu II ions while retaining the integrity of the network.